2003
DOI: 10.1021/jf0261497
|View full text |Cite
|
Sign up to set email alerts
|

Sulfosulfuron Incorporated in Micelles Adsorbed on Montmorillonite for Slow Release Formulations

Abstract: Slow release formulations of the anionic herbicide sulfosulfuron (SFS) were prepared by incorporating it in micelles of an organic cation octadecyltrimethylammonium, which adsorb on the clay-mineral montmorillonite. The fraction of SFS adsorbed on the micelle-clay complex reached 98%, whereas for monomer-clay complexes, its adsorption was insignificant. Fluorescence studies showed surface contact between the micelles and the clay surface. The rate of SFS release from the micelle-clay formulations in aqueous su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Water movement modified by sorption and transformation processes apart from soil physical and chemical properties mainly influences herbicide transport and accumulation in soils and ground water. The mobility of residues in subsoil thus depends on the adsorption and desorption characteristics (Undabeytia, Mishael, Nir, Papahadjopoulus Stenberg, Rubin, Morillo et al, 2003;Mishael, Undabeytia, Rabinovitz, Rubin, & Nir, 2003). The residues adsorbed on the soil surface are vulnerable for sunlight exposure resulting their photochemical degradation.…”
Section: Stability Of Sulfosulfuronmentioning
confidence: 99%
“…Water movement modified by sorption and transformation processes apart from soil physical and chemical properties mainly influences herbicide transport and accumulation in soils and ground water. The mobility of residues in subsoil thus depends on the adsorption and desorption characteristics (Undabeytia, Mishael, Nir, Papahadjopoulus Stenberg, Rubin, Morillo et al, 2003;Mishael, Undabeytia, Rabinovitz, Rubin, & Nir, 2003). The residues adsorbed on the soil surface are vulnerable for sunlight exposure resulting their photochemical degradation.…”
Section: Stability Of Sulfosulfuronmentioning
confidence: 99%
“…Bentonite is a natural material containing montmorillonite as a major constituent and has been considered as a potential adsorbent or carrier for many chemicals due to the high specific surface area and particular surface properties (Zhu et al, 2003b;Xu and Zhu, 2007;Paiva et al, 2008;Ijagbemi et al, 2009). Bentonite has been used in CRF of insecticides and herbicides, and has succeeded in reducing the leaching of active ingredients in soil (Polubesova et al, 2001(Polubesova et al, , 2003Mishael et al, 2002Mishael et al, , 2003Rytwo et al, 2005Rytwo et al, , 2008Li et al, 2009;Singh et al, 2009Singh et al, , 2010. However, the intrinsic hydrophilicity of bentonite makes it an ineffective sorbent for hydrophobic organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Mepiquat (Polubesova et al, 2001), berberine (Rytwo et al, 2005(Rytwo et al, , 2008 and quaternary ammonium surfactants (Mishael et al, 2002(Mishael et al, , 2003Polubesova et al, 2003) have turned out to be effective modifying agents to increase the adsorption capacity of bentonite towards several herbicides and reduce the leaching in soil. However, knowledge about the structural effects on the controlled release of pesticide from organobentonite is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that incorporation of active ingredients in the micelles and vesicles formed by surfactant molecules which adsorbed on clays, such as montmorillonite, provided a slow release system [14][16]. The fraction of the pesticide encapsulated in surfactant-clay complexes prolonged their action.…”
Section: Introductionmentioning
confidence: 99%